Question
Asked Oct 8, 2019
6 views

f(x) = -2x+1 and g (x)=x-9/2

(a) ( f o g )(x) =

(b)( g o f )(x)=

(c) thus g(x) =       an inverse function of f(x)n 

check_circle

Expert Answer

Step 1

(a)

The given function:

The given function is f(x)=-2x +1 and g (x) = X-9.
2
Find the value of the given function as follows
(f g (x)=f(g(x))
х -9
-2
1
2
=-x+ 9+1
=-x+10
help_outline

Image Transcriptionclose

The given function is f(x)=-2x +1 and g (x) = X-9. 2 Find the value of the given function as follows (f g (x)=f(g(x)) х -9 -2 1 2 =-x+ 9+1 =-x+10

fullscreen
Step 2

(b)

The given fun...

х -9
The given function is f(x)=-2x +1 and g(x) =
2
Find the value of the given function as follows
(gof(x)-g(f(x))
-2х +1-9
2
—2х — 8
2
-2(x+ 4)
2
—-х—4
help_outline

Image Transcriptionclose

х -9 The given function is f(x)=-2x +1 and g(x) = 2 Find the value of the given function as follows (gof(x)-g(f(x)) -2х +1-9 2 —2х — 8 2 -2(x+ 4) 2 —-х—4

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour.*

See Solution
*Response times may vary by subject and question.
Tagged in

Math

Algebra

Other

Related Algebra Q&A

Find answers to questions asked by student like you

Show more Q&A add